2011
DOI: 10.30950/jcer.v7i1.275
|View full text |Cite
|
Sign up to set email alerts
|

National Coordination of EU Policy: A Comparative Study of the Twelve “New” Member States

Abstract: European Union policy-making requires Member States to determine national positions by means of national coordination in order to defend their preferences. This article analyses the coordination systems of the twelve "new" Member States in the middle of 2009 and compares them along the two major lines of divergence in coordination systems: their centralisation and their coordination ambition. In so doing, it ties in with a framework developed by Kassim (2003) and plots the new Member States in a diagram which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 25 publications
1
5
0
1
Order By: Relevance
“…CODEF did not have sufficient political or policy influence to ensure effective coordination across government ministries and agencies, in particular to overcome entrenched institutional resistance and traditional ways of working among officials that did not encourage information-sharing or cooperation. As such, the research supports findings for other Central and Eastern European countries relating to the importance of political and administrative opportunity structures in explaining variation in coordination (Gärtner et al 2011), but it also substantiates the arguments of Dimitrova and Toshkov (2007) that actors' preferences and domestic politics are key factors influencing patterns and processes of institutional change.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…CODEF did not have sufficient political or policy influence to ensure effective coordination across government ministries and agencies, in particular to overcome entrenched institutional resistance and traditional ways of working among officials that did not encourage information-sharing or cooperation. As such, the research supports findings for other Central and Eastern European countries relating to the importance of political and administrative opportunity structures in explaining variation in coordination (Gärtner et al 2011), but it also substantiates the arguments of Dimitrova and Toshkov (2007) that actors' preferences and domestic politics are key factors influencing patterns and processes of institutional change.…”
Section: Discussionsupporting
confidence: 84%
“…Coordination capability is regarded as one four key essential requirements for effective administrative capacity (Hertie School of Governance 2013). The accession countries of Central and Eastern Europe have faced the challenge of establishing the necessary coordination structures prior to their accession, which in many cases involved a paradigm shift from a hierarchical, legalistic and centralised yet ineffective planning to more inclusive, accountable and network modes of coordination -albeit with very different outcomes in terms of the structures, functioning and effectiveness of national coordination systems (Dimitrova and Toshkov 2007;Gärtner et al 2011). Similar challenges apply to candidate countries in South-East Europe (SEE).…”
mentioning
confidence: 99%
“…However, coordination with regard to the negotiations in the Council is the intersection common to all (Kassim et al 2000;Kassim et al 2001;Bulmer and Burch 2001;Wessels et al 2003;Kassim 2003a;Blumer and Lequesne ed. 2005;Dimitrova and Toshkov 2007;Fink-Hafner 2007;Panke 2010;Johansson and Raunio 2010;Gärtner et al 2011). Although the analytical vocabulary differs, the studies all draw similar conclusions, finding few signs of convergence between national coordination mechanisms.…”
mentioning
confidence: 82%
“…More recent research, however, demonstrated the continuous relevance of the distinction between centralized and decentralized coordination (Jensen, 2014; Kassim, 2015). Despite its lower efficiency, some newer member states such as Romania or Slovakia deliberately adopted the decentralized, ministry‐focused model (Gärtner et al, 2011). On the other hand, the more Eurosceptic a member state's electorate and the higher the salience of EU policies, the likelier a centralization of coordination around the prime minister's office (Jensen, 2017; Kaniok and Galušková, 2018).…”
Section: Decentralized Eu Policy Coordination In the Polycrisismentioning
confidence: 99%